// End script hiding -->
SOLUTION: x^2+9x-12=0 x^2=9x=12 4x^2+36x=12x4 4x^2+36x=48 4x^2+36x+6=48+6 and this is where i get completely confused...i don't even know if I've done the problem right thus far. yo
Algebra
->
Quadratic Equations and Parabolas
->
Quadratic Equation Customizable Word Problems
-> SOLUTION: x^2+9x-12=0 x^2=9x=12 4x^2+36x=12x4 4x^2+36x=48 4x^2+36x+6=48+6 and this is where i get completely confused...i don't even know if I've done the problem right thus far. yo
Log On
Ad:
You enter your algebra equation or inequality -
Algebrator
solves it step-by-step while providing clear explanations. Free on-line demo
.
Ad:
Mathway
solves algebra homework problems with step-by-step help!
Quadratics: solvers
Quadratics
Practice!
Practice
Answers archive
Answers
Lessons
Lessons
Word Problems
Word
In Depth
In
Immediate math help from PAID TUTORS
. (paid link)
Click here to see ALL problems on Quadratic Equations
Question 385519
:
x^2+9x-12=0
x^2=9x=12
4x^2+36x=12x4
4x^2+36x=48
4x^2+36x+6=48+6
and this is where i get completely confused...i don't even know if I've done the problem right thus far. your suggestions please???
Answer by
stanbon(69061)
(
Show Source
):
You can
put this solution on YOUR website!
x^2+9x-12=0
Use the quadratic formula:
x = [-b +- sqrt(b^2-4ac)]/(2a)
-----------------------------------
x = [-9 +- sqrt(81 - 4*1*-12)]/2
---
x = [-9 +- sqrt(129)]/2
----
x = [-9 +- 11.36]/2
---
x = [2.36/2] or x = [-20.36/2]
---
x = 1.18 or x = -10.18
============================
cheers,
Stan H.